Optimal electricity supply system under Iranian framework limitations to meet its emission pledge under the Paris climate agreement - Ali Abbasi Godarzi; Abbas Maleki (International Journal of Sustainable Energy Planning and Management, 2021)
As part of its Paris Agreement commitment, Iran pledged to decrease 4 percent of its carbon dioxide (CO2) emissions from 2020 to 2030. About 29% of total emission in Iran belongs to electricity supply while energy consumption in other sectors (transport, household, and industry) have a lower share in CO2 emission. The main concern here is finding the optimal mix of power plants in the electricity supply system that should be deployed to meet Iran’s mentioned respective targets. So, we developed a non-linear mathematical programming model for Iran’s electricity system to address this concern. Results show that a 10-20% diffusion of renewable energy and converting gas turbine power plants to gas combined cycle technology with 5% annual rate can satisfy Iran’s emissions pledge under the Paris Climate Accord. Finally, this model has been run for years between 2017-2030. Four scenarios have also been prepared based on different Iranian Five-Year Development Plans.